Bioremediation of Pollutants in Soil and Water 1995
DOI: 10.1520/stp13033s
|View full text |Cite
|
Sign up to set email alerts
|

Rhizosphere Microbial Communities of Herbicide-Tolerant Plants As Potential Bioremedients of Soils Contaminated with Agrochemicals

Abstract: Plant roots influence the soil in which they grow in a variety of ways, making the soil more conducive for microbial growth and activity, as well as cometabolic reactions. Studies examining the fate of pesticides in plant-soil systems have revealed a marked decrease in persistence of these compounds. Additionally, similar observations have recently been made for oil residues, polycyclic aromatic hydrocarbons, trichloroethylene, and surfactants. These previous studies suggest that the root zone could potentiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Herbicide and pesticide contamination is usually too expensive to clean up with current mentioned technologies. Studies have shown that certain tolerant plants and microbes can be used in biological remediation which can be cost-effective and simpler, due to the in-situ advantage, pollution can be exacerbated by the pesticides/herbicides involved, but these, too can be remediated through biological remediation (Perkovich et al 1996;Kruger et al 1997;Anderson et al 1995). Most of the naturally occurring microorganisms are selected on conventional culture media which has many drawbacks for the selection.…”
Section: Phytoremediation Of Herbicides and Pesticidesmentioning
confidence: 99%
“…Herbicide and pesticide contamination is usually too expensive to clean up with current mentioned technologies. Studies have shown that certain tolerant plants and microbes can be used in biological remediation which can be cost-effective and simpler, due to the in-situ advantage, pollution can be exacerbated by the pesticides/herbicides involved, but these, too can be remediated through biological remediation (Perkovich et al 1996;Kruger et al 1997;Anderson et al 1995). Most of the naturally occurring microorganisms are selected on conventional culture media which has many drawbacks for the selection.…”
Section: Phytoremediation Of Herbicides and Pesticidesmentioning
confidence: 99%
“…Accelerated mineralization of pesticides has also been found in the rhizosphere of plants from pesticidecontaminated sites. Anderson and co-workers [22,53] Wetland plants may also be utilized to remediate contaminated water and soil. Like terrestrial plants, aquatic macrophytes are capable of taking contaminants up in their tissues and enhancing biodegradation in the rhizosphere.…”
Section: Rhizospherementioning
confidence: 99%